Correlation between umbilical venous blood gas at birth and comorbidities in preterm babies - A cohort study - Gopinath, Reetha; Jacob, Ambili Susan; Gangadharan, Anu; Aslesh, O P (Indian Journal of Child Health, 2022)
Background: Umbilical cord blood gas analysis is a useful tool in predicting short-term outcomes in term infants. The value of umbilical venous blood gas analysis in predicting short-term outcomes in preterm infants is less clear. Objectives: The study was carried out to determine the correlation between venous blood gases and various antenatal and natal characteristics as well as short term comorbidities in preterm infants born before 34 weeks of gestation. Methods: In a cohort study, 74 preterm infants born before 34 weeks of gestation were enrolled, and umbilical venous blood gas analysis was performed within 1 h of birth. All preterm infants with pH 4 mmol/L and bicarbonate 4 mmol/L and bicarbonate 4 mmol/L showed a significant association with neonatal death (p=0.01) and thrombocytopenia was significantly associated with bicarbonate